2019
DOI: 10.1186/s13063-019-3922-2
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality as an adjunct to anesthesia in the operating room

Abstract: BackgroundAdvancements in virtual reality (VR) technology have resulted in its expansion into health care. Preliminary studies have found VR to be effective as an adjunct to anesthesia to reduce pain and anxiety for patients during upper gastrointestinal endoscopies, dental procedures and joint arthroplasties. Current standard care practice for upper extremity surgery includes a combination of regional anesthesia and intraoperative propofol sedation. Commonly, patients receive deep propofol sedation during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Eleven studies describe how XR can modulate pain for patients. XR has been used to supplement sedative and pain relief processes prior to [32], during [33], and after surgery [34]. VR has been the most prevalent form of XR used, inducing a meditative state during or after the surgery.…”
Section: Painmentioning
confidence: 99%
“…Eleven studies describe how XR can modulate pain for patients. XR has been used to supplement sedative and pain relief processes prior to [32], during [33], and after surgery [34]. VR has been the most prevalent form of XR used, inducing a meditative state during or after the surgery.…”
Section: Painmentioning
confidence: 99%
“…While in cardiology, the majority of devices are intended to monitor heart rhythm, others have a therapeutic purpose [8][9][10]. One such device, the virtual reality headset, is the subject of numerous studies [11][12][13][14][15] and has recently shown to improve analgesia in a small sample of patients undergoing transcatheter aortic valve implantation [16,17]. To our knowledge, this device has not been tested in other cardiac procedures.…”
Section: Introductionmentioning
confidence: 99%
“…VR technology has been widely used in clinical practice, such as treating the mental illness, reducing preoperative anxiety in patients [20][21][22][23][24]38]. Shah et al [39], found that stress was the primary target while depression was the secondary in the VR mood induction procedure study.The current study would be a positive result adding to the evidence that VR technology can be used as a effective measure to reduce the stress of night shift anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%